2016
DOI: 10.1038/bjc.2016.166
|View full text |Cite
|
Sign up to set email alerts
|

Definitive chemoradiation alters the immunologic landscape and immune checkpoints in head and neck cancer

Abstract: Background:Preclinical and clinical studies suggest potential synergy between high dose per fraction focal radiation and immunotherapy. However, conventionally fractionated radiation regimens in combination with concurrent chemotherapy are more commonly administered to patients as definitive treatment and may have both immune-stimulating and -suppressive effects.Methods:We prospectively collected longitudinal samples from head and neck squamous cell carcinoma patients receiving definitive radiation therapy. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 57 publications
4
48
1
1
Order By: Relevance
“…70 In a clinical study in HNSCC patients, PD-1 expression on peripheral immune cells also increased during chemoradiation. 71 Together, these findings support the concept of adding anti-PD1/PD-L1 treatment to RT for HNSCC.…”
Section: Concurrent Radiation With Anti-pd1/pd-l1 Therapy For Hnsccsupporting
confidence: 61%
See 1 more Smart Citation
“…70 In a clinical study in HNSCC patients, PD-1 expression on peripheral immune cells also increased during chemoradiation. 71 Together, these findings support the concept of adding anti-PD1/PD-L1 treatment to RT for HNSCC.…”
Section: Concurrent Radiation With Anti-pd1/pd-l1 Therapy For Hnsccsupporting
confidence: 61%
“…In an animal model, PD‐L1 expression increased after radiation; and adding an anti‐PD‐L1 agent to RT improved efficacy . In a clinical study in HNSCC patients, PD‐1 expression on peripheral immune cells also increased during chemoradiation . Together, these findings support the concept of adding anti‐PD1/PD‐L1 treatment to RT for HNSCC.…”
Section: Concurrent Radiation With Anti‐pd1/pd‐l1 Therapy For Hnsccmentioning
confidence: 60%
“…In fact, 82% of responders in our cohort received prior platinum-based therapy. Interestingly, platinum-based therapies are not often considered immunogenic chemotherapeutic agents (15), but it may be that the addition of concurrent radiotherapy enhances their immunogenic potential (16).…”
Section: Discussionmentioning
confidence: 99%
“…[17, 20] Serum CXCL10 concentration, but not CXCL9, was reportedly correlated with the number of circulating lymphocytes in head and neck cancer with radiation therapy. [21] Ming-Fang et al revealed that CXCL10-deficient mice had higher mortality rate with the dengue virus infection. [22]…”
Section: The Expression and Implication Of Cxcl9 Cxcl10 Cxcl11 Andmentioning
confidence: 99%